Analysis of MEMS Fluxgate Design for Vibration and Impact; Materials Science Forum; Vol. 970 : Modern Problems in Materials Processing, Manufacturing, Testing and Quality Assurance II - Baranov P. F. Pavel Fedorovich (2019, 2019)
Title screen